Psicologia e Neurociência: Uma Avaliação da Perspectiva Materialista no Estudo dos Fenômenos Mentais [Psychology and Neuroscience: An Assessment of the Materialist Perspective in the Study of Mental Phenomena] by Saulo de Freitas Araujo - Shimabucuro, Alessandro H. (Journal of Scientific Exploration, 2012)
Psicologia e Neurociência [Psychology and Neuroscience] is a book that offers interesting and fruitful contributions to current studies involving the mind–brain question. Starting from a critical analysis of the materialist perspective in the light of the philosophy of mind, psychology, and neuroscience, it promotes a debate on the language used in the description of mental phenomena and scientific experimental procedures for studying these same phenomena.